Chemical composition of the ctenophore Mnemiopsis leidyi and evaluation of lts role in transformation of biogenic elements in the Black Sea. - Borodkin, Sergey O; Korzhikova, L I (PANGAEA, 1991)
Data of chemical analysis of Black Sea ctenophore Mnemiopsis leidyi indicates that their body contains on average 5.28% carbon, 3.48% nitrogen, 0.11% phosphorus, and 0.03% silicon on dry weight. Mean ratios of the main biogenic elements in ctenophores is C:N=1.4, N:P=10.9, and C:P=32.2. Comparing concentration of the main biogenic elements in the surface layer with their concentrations in ctenophores it is concluded that mass development of M. leidyi has negative effect on the hydrochemical structure of the Black Sea.
(Table 1) Variation in chemical composition of Black Sea ctenophores depending on size
Keywords: Archive of Ocean Data; ARCOD; Black Sea; Carbon; DM44-4128; DM44-4133; DM44-4134; DM44-4141; DM44-4143; Dry mass; Element analyser CHN; MULT; Nitrogen, total; Phosphorus; Silicon; Wet chemistry; Wet mass